The impact of the mechanical whole-body vibration experienced during military land transit on the physical attributes underpinning dismounted combatant physical performance: A randomised controlled trial. Issue 4 (April 2021) - Debenedictis, Thomas A.; Billing, Daniel; Milanese, Steven; Furnell, Alistair; Tomkinson, Grant; Thewlis, Dominic
Abstract: Objectives: The aim of this randomised controlled trial was to explore the impact of the mechanical WBV experienced during simulated military land transit on the physical attributes that underpin tasks performed by dismounted combatants. Design: This study used a parallel group randomised control trial design. Methods: Sixty participants were randomly assigned to one of four, 2-h laboratory-based simulations (restricted posture, sealed road, cross country or a control condition). A smaller sample of 16 Australian Defence Force infantry personnel served as a validation group and were exposed to the same conditions. Neither the restricted posture nor the control conditions were exposed to any WBV, but the former were secured in place using the built-in seat harness. Prior to, and following the assigned condition, participants performed a series of battlefield relevant physical performance tests including; drop jump, 20-m sprint, reactive agility, arm-hand steadiness, isometric mid-thigh pull, and sit-and-reach. Results: Medium decreases in the drop jump were observed for both the sealed road (effect size [ES] = 0.53) and cross-country (ES = 0.97) simulation conditions indicating a decrease in performance of the jump phase. A large decrease in 20-m sprint performance was observed in both the sealed road (ES = 1.37) and cross-country (ES = 0.88) exposure conditions. Additionally, a large decrease in 20-m sprint performance was observed for the restricted posture (ES = 1.02) exposure condition. Conclusions: These findings indicate that exposure to WBV experienced during motorised land transit has a negative influence on aspects of lower body explosive strength.